Elevated Soluble Fas and FasL in Cerebrospinal Fluid and Serum of Patients With Anti-N-methyl-D-aspartate Receptor Encephalitis - Ding, Yue-Wen; Pan, Su-Yue; Xie, Wei; Shen, Hai-Ying; Wang, Hong-Hao (Frontiers in Neurology, 2018)
Objective: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is a severe autoimmune disorder that mainly affects children and young women. The Fas system contains both membrane-bound versions of Fas (mFas) and Fas ligand (mFasL), and soluble versions (sFas and sFasL), which play important roles in apoptosis and regulation of the immune system. Both the levels of sFas and sFasL and the role they play in anti-NMDAR disease pathogenesis remain unclear. Methods: Forty-eight pairs of cerebrospinal fluid (CSF) and serum were collected from patients with anti-NMDAR encephalitis, encephalitis of other causes or peripheral neuropathy. The CSF and serum concentrations of sFas and sFasL were determined with enzyme-linked immunosorbent assay. Results: CSF concentrations of sFas and sFasL were both incresased in anti-NMDAR encephalitis patients compared with controls patients. Serum sFas levels were also elevated in anti-NMDAR encephalitis patients relative to controls. sFas and sFasL concentrations in CSF positively correlated with the modified Rankin scale (mRS) both at onset and 6-month follow-up. Conclusion: CSF sFas and sFasL levels were elevated in anti-NMDAR encephalitis patients, and reflect the disease severity of anti-NMDAR encephalitis.